Impact cost of the product on the effectiveness of business organizations - A. S. Senin (Модернизация, инновация, развитие, 2016)
One of the key elements of managing the operations of the organization - management costs, as the costs, representing the payment that needs to be done to attract and retain economic resources, are one of the main factors determining the size of the financial results of the organization, return on invested capital, and, ultimately, the value of the business.Objectives. The aim of this work is to study the influence of the structure of production costs on the profitability of products.Method’s. To complete this article were used such methods of analysis as legal, comparative, economic-statistical and correlation.Conclusions / significance. The practical value of this work lies in the fact that in the article the notion and cogs, equations of linear regression between the proportion of costs in the cost and profitability of products by types of economic activity in the Russian Federation in 2012, the Obtained models allow knowing the share of costs in the cost structure for different types of economic activities in the Russian Federation in 2012 to estimate the average level of profitability of production.